Bi-allelic Mutations in TTC21A Induce Asthenoteratospermia in Humans and Mice - Liu, Wangjie; He, Xiaojin; Yang, Shenmin; Zouari, Raoudha; Wang, Jiaxiong; Wu, Huan; Kherraf, Zine-Eddine; Liu, Chunyu; Coutton, Charles; Zhao, Rui; Tang, Dongdong; Tang, Shuyan; et al. (American journal of human genetics, 2019)
Male infertility is a major concern affecting human reproductive health. Asthenoteratospermia can cause male infertility through reduced motility and abnormal morphology of spermatozoa. Several genes, including DNAH1 and some CFAP family members, are involved in multiple morphological abnormalities of the sperm flagella (MMAF). However, these known genes only account for approximately 60% of human MMAF cases. Here, we conducted further genetic analyses by using whole-exome sequencing in a cohort of 65 Han Chinese men with MMAF. Intriguingly, bi-allelic mutations of TTC21A (tetratricopeptide repeat domain 21A) were identified in three (5%) unrelated, MMAF-affected men, including two with homozygous stop-gain mutations and one with compound heterozygous mutations of TTC21A. Notably, these men consistently presented with MMAF and additional abnormalities of sperm head-tail conjunction. Furthermore, a homozygous TTC21A splicing mutation was identified in two Tunisian cases from an independent MMAF cohort. TTC21A is preferentially expressed in the testis and encodes an intraflagellar transport (IFT)-associated protein that possesses several tetratricopeptide repeat domains that perform functions crucial for ciliary function. To further investigate the potential roles of TTC21A in spermatogenesis, we generated Ttc21a mutant mice by using CRISPR-Cas9 technology and revealed sperm structural defects of the flagella and the connecting piece. Our consistent observations across human populations and in the mouse model strongly support the notion that bi-allelic mutations in TTC21A can induce asthenoteratospermia with defects of the sperm flagella and head-tail conjunction.